THE INFLUENCE OF DIGITAL LITERACY ON TEACHER’S TECHNOLOGY PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) WITH WORK MOTIVATION AS A MEDIATING VARIABLE: (Survey Pada Guru di SMP Sederajat di Kecamatan Hantara) - Afifah Zayanah; Agie Hanggara; Atin Nuryatin (Institut Pendidikan Indonesia, 2026)
This study is motivated by the low ability of teachers to integrate technology, pedagogy, and content knowledge (TPACK) in the digital era. The research is grounded in the theoretical framework of TPACK, digital literacy, and work motivation as a psychological factor influencing teacher performance. This study aims to analyze the effect of digital literacy on TPACK with work motivation as a mediating variable among SMP/MTs teachers in Hantara District. The research employs a quantitative descriptive method with a survey approach. Data were collected through questionnaires and analyzed using path analysis. The findings reveal that digital literacy has a positive and significant effect on teachers’ TPACK. In addition, digital literacy also influences work motivation, which in turn significantly mediates the relationship between digital literacy and TPACK. These results indicate that improving digital literacy not only directly enhances teachers’ technical competencies but also strengthens work motivation, which encourages innovation in teaching practices. Therefore, strengthening digital literacy and work motivation is essential to improve teacher professionalism and the quality of learning in the digital era.